HUBUNGAN KONSUMSI MAKANAN LAUT DENGAN KEJADIAN HIPERTENSI PADA MASYARAKAT PESISIR DI WILAYAH KERJA PUSKESMAS MANGKANG KOTA SEMARANG - Retno Cahyani; Lintang Dian Saraswati; Praba Ginandjar (Jurnal Kesehatan Masyarakat, 2019)
Abstract : The risk of hypertension for people who consume more than 6 grams of salt per day 5-6 times greater, compared with people who consume low amounts of salt. Semarang. The design of this study was analytic with cross sectional approach. The sample of this research is 100 people with age range 18-64 years who meet the criteria of being subject of research. The sampling method used, the instrument used was a questionnaire. The results of the study there  is a very significant relationship between seafood consumption with the incidence of hypertension (p = 0.002). Based on the results of the study, the conclusion that the majority of respondents suffer from hypertension> 2 years as many as 32 respondents (64%), and the majority consume daily <2 pieces and frequency <4 times a week as many as 27 respondents (54.0%), and therefore should be expected to Puskesmas staff to provide counseling in the form of good ways to consume seafood containing high sodium.